What went right during the COVID crisis: The capabilities of local actors and lasting innovations in oncology care and research. - Brenda Bogaert; Zisis Kozlakidis; Elodie Caboux; Julien Péron; Pierre Saintingy (Public Library of Science (PLoS), 2023)
This article will elaborate how oncology care and research was adapted during the COVID pandemic in the Metropole of Lyon (France), including the lasting innovations that came out of the crisis. The research method involved 22 semi-structured qualitative interviews of healthcare professionals, managers, and researchers in the Lyon, France region coming from both public and private academic hospitals. The interviews took place from February 2021-December 2022 in order to assess the long-term adaptations and innovations in cancer care organization in the post-COVID era. The main results show adaptations and innovations in 1) new processes and resources to facilitate disciplinary and interdisciplinary work; 2) harmonization and streamlining of patient journeys. In the discussion section, we will mobilize the capabilities approach, an interdisciplinary social sciences approach that focuses on the capabilities of persons to be and to do, to elaborate the conditions by which local actors were able to be agile, to adapt and to innovate in spite of the healthcare emergency and in coherence with their professional and personal values.